Influence of Household Water Filters on Bacteria Growth and Trace Metals in Tap Water of Doha, Qatar - Jerome Nriagu (1790893) (2018)
Deteriorating water quality from aging infrastructure, growing threat of pollution from industrialization and urbanization, and increasing awareness about waterborne diseases are among the factors driving the surge in worldwide use of point-of-entry (POE) and point-of-use (POU) filters. Any adverse influence of such consumer point-of-use systems on quality of water at the tap remains poorly understood, however. We determined the chemical and microbiological changes in municipal water from the point of entry into the household plumbing system until it leaves from the tap in houses equipped with filters. We show that POE/POU devices can induce significant deterioration of the quality of tap water by functioning as traps and reservoirs for sludge, scale, rust, algae or slime deposits which promote microbial growth and biofilm formation in the household water distribution system. With changes in water pressure and physical or chemical disturbance of the plumbing system, the microorganisms and contaminants may be flushed into the tap water. Such changes in quality of household water carry a potential health risk which calls for some introspection in widespread deployment of POE/POU filters in water distribution systems. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41598-018-26529-8